Comparative Analysis of Dijkstra and A* Algorithms for Determining the Shortest Route from SMKN 9 Medan to Gramedia Gajah Mada - Ardiansyah, Ardiansyah (Journal of Computer Science and Research (JoCoSiR), 2025)
Determining the shortest route is an important problem in navigation system development, especially in urban environments with complex road networks. This study aims to compare the performance of the Dijkstra algorithm and the A* algorithm in finding the shortest route from SMKN 9 Medan to Gramedia Gajah Mada. Distance data between nodes and heuristic values were obtained from Google Maps and represented in a graph structure for route computation. Both algorithms were applied to three predetermined route alternatives. The results show that Dijkstra and A* produced the same optimal route, namely A–B–E–G, with a total distance of 5.7 km. However, the A* algorithm demonstrated higher efficiency by exploring fewer nodes and requiring less computational time due to the use of a heuristic function. Therefore, the A* algorithm is more suitable for intelligent navigation systems requiring faster computation, while the Dijkstra algorithm is more appropriate for smaller networks without heuristic considerations.